The 677 C/T MTHFR polymorphism is associated with essential hypertension, coronary artery disease, and higher homocysteine levels - Ilhan, Nevin; Kucuksu, Mehmet; Kaman, Dilara; Ilhan, Necip; Ozbay, Yilmaz (Elsevier Science Inc, 2008)
Background. Essential hypertension (EH) and cardiovascular disease are common, multifactorial disorders likely to be influenced by multiple genes of modest effect. The C677T methylenetetrahydrofolate reductase (MTHFR) gene polymorphism is related to MTHFR enzyme activity and to plasma homocysteine (Hcy) concentration. This study was designed to investigate an association of this polymorphism with coronary artery disease (CAD), EH, and healthy subjects. Methods. In this study, we measured serum folate, serum vitamin B12, and plasma homocysteine and determined the MTHFR C677T genotype of 78 patients with essential hypertension, 100 patients with coronary artery disease, and 100 healthy subjects. MTHFR genotypes were assessed by real-time polymerase chain reaction. Results. CC, CT, and TT genotype frequencies were 52, 44.0, and 4.0% in patients with CAD, respectively. In patients with essential hypertension, the CC, CT, and TT genotype frequencies were 46.2, 41.0, and 12.8%, respectively. In control subjects, the CC, CT, and TT genotype frequencies were 72.0, 26.0, and 2.0%, respectively. The C allele was significantly more frequent in controls compared with patients with EH (p <0.05), and CC genotypes were more frequent in controls compared to patients with EH and CAD. Homocysteine level was higher in TT genotypes in CAD patients compared with CC and CT genotypes (p <0.01). MTHFR gene polymorphism is an independent risk factor for EH but not for CAD. Conclusions. The TT genotype of the 677C/T MTHFR polymorphism is associated with EH and CAD. In addition, TT genotypes had higher plasma Hcy levels in CAD patients compared with CC and CT genotypes. MTHFR gene polymorphism is an independent risk factor for EH but not for CAD. (C) 2008 IMSS. Published by Elsevier Inc.
Keywords: MTHFR gene polymorphism; essential hypertension; coronary artery disease